Aplikasi Akademik Berbasis Website Menggunakan Metode Extreme Programming Pada SMAN1 Belinyu - Fenardi, Okky; Lee, Francka Sakti (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
The development of information technology provides many changes in human life today, one of them is in the education field. SMAN1 Belinyu is one of many educational institutions that is able to utilize this information technology to assist school business process activities. Therefore, it is necessary to design an academic application to support teaching and learning activities at SMAN1 Belinyu. The data collection in this research is done by literature study and interviews with relevant sources. This academic application is built with Extreme Programming method that allows the development of applications to be flexible with changing needs. The research resulted in an academic application that facilitates the management of school data and integration of data management with the application system that is already running. This application will be used by administrators, teachers, students, and library staffs. Based blackbox testing results, all academic application functions have run well and provide results as expected. To conclude this research, the development of this academic application is able to overcome the problems faced by SMAN1 Belinyu and help the process of managing data and teaching and learning activities.